Analysis of Factors that Influence Dividend Payout Ratio of Coal Companies in Indonesia Stock Exchange - Kusuma, Pradana Jati; Hartoyo, Sri; Sasongko, Hendro (JDM (Jurnal Dinamika Manajemen), 2018)
The purpose of this study is to analyze the company’s internal and macroeconomic conditions on the ratio of dividend distribution, as well as knowing the conditions of coal companies on the IDX during the decline in coal prices. The weakening of the global economy has resulted in a decline in various commodity prices, including coal prices. Various studies were conducted to determine the factors that influence the poor condition of sectoral mining indices in these weakening conditions a few years ago. The coal subsector has the largest capitalization in the mining sector. Multiple regression models are used to analyze 55 samples from 11 coal subsector companies. The research period was carried out from 2013 to 2017. The results showed that return on assets, exchange rates, world oil prices had a positive and significant partial effect on the dividend payout ratio of the coal subsector. The implications of the findings are management of coal subsector company needs to pay attention to internal and external factors so that they can distribute dividends regularly.